Development of a Plasmodium vivax malaria model for evaluating the effects of control strategies on the malaria burden in Democratic People’s Republic of Korea - Seong, Hye; Suh, Jiyeon; Choi, Jun Yong; Lee, Jeehyun; Yeom, Joon-Sup (Frontiers in Public Health, 2024)
Background Plasmodium vivax malaria has been one of the most troublesome diseases in the Democratic People’s Republic of Korea (DPRK). Given that a majority of malaria cases are concentrated near the demilitarized zone, concerted elimination efforts from both the Republic of Korea (ROK) and DPRK are essential for a malaria-free Korean Peninsula. This study assessed the impact of rapid diagnostic tests (RDTs) and tafenoquine on malaria incidence in DPRK. Methods We patterned the current model structure from the previously developed Plasmodium vivax malaria dynamic transmission model for ROK. Model parameters were adjusted using demographic and climate data from malaria-risk areas in DPRK, and the model was calibrated to annual malaria incidences from 2014 to 2018 in DPRK, as reported by the World Health Organization. Subsequently, we estimated the preventable malaria cases over a decade after introducing RDTs and tafenoquine compared to using microscopy alone and primaquine, respectively. Sensitivity analysis was performed to account for uncertainty in model parameters. Results When comparing RDTs to microscopy, a one-day reduction in diagnostic time due to the introduction of RDTs led to a reduction in malaria incidence by 26,235 cases (65.6%) over the next decade. With a two-day reduction, incidences decreased by 33,635 (84.1%). When comparing a single dose of tafenoquine with a 14-day primaquine regimen, the former prevented 1,222 (77.5%) relapse cases and 4,530 (11.3%) total cases over the years. Conclusion The continuous and simultaneous implementation of RDTs and tafenoquine emerges as a potent strategy to considerably reduce malaria in DPRK.